2017
DOI: 10.15446/agron.colomb.v35n1.58586
|View full text |Cite
|
Sign up to set email alerts
|

High dilution preparations for organic production system of broccoli

Abstract: The aim of this study was to evaluate the influence of high dilution preparations on seedlings growth and production of broccoli under organic system. Three experiments were conducted in a greenhouse with completely randomized design. Two others experiments were conducted under field conditions, and the experimental design was randomized in blocks. Both designs were done with four replications and nine treatments. The treatments consisted of high dilution preparations of Arnica montana, Silicea terra, Carbo ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
4
0
3
Order By: Relevance
“…In this context, agro-homeopathy could be an integrative approach to improve organic agriculture since homeopathic treatments, due to their ultrahigh dilutions, have few or no ecological side effects. In recent years there has been a growing interest of the scientific community in such methods, and many scientific studies have been performed to evaluate the effect of homeopathic treatments on plants [1][2][3][4][5][6][7][8][9][10]. Different plant model systems have been set up both in basic research (in vitro germination and growth models with healthy, impaired, and phytopathological models) [1][2][3][4][5] and in application research (field trials) [2].…”
Section: Homeopathy In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, agro-homeopathy could be an integrative approach to improve organic agriculture since homeopathic treatments, due to their ultrahigh dilutions, have few or no ecological side effects. In recent years there has been a growing interest of the scientific community in such methods, and many scientific studies have been performed to evaluate the effect of homeopathic treatments on plants [1][2][3][4][5][6][7][8][9][10]. Different plant model systems have been set up both in basic research (in vitro germination and growth models with healthy, impaired, and phytopathological models) [1][2][3][4][5] and in application research (field trials) [2].…”
Section: Homeopathy In Agriculturementioning
confidence: 99%
“…Different plant model systems have been set up both in basic research (in vitro germination and growth models with healthy, impaired, and phytopathological models) [1][2][3][4][5] and in application research (field trials) [2]. Experimental research on healthy and stressed plants has shown the potential of homeopathic treatments to influence plants by enhancing growth parameters, increasing germination rate and defensive substances, and strengthening plants against pathogen and pest attacks [6][7][8][9][10].…”
Section: Homeopathy In Agriculturementioning
confidence: 99%
“…se ao controle de pragas, como pulgões (WYSS et al, 2010), fungos (TREBBI et al, 2016), incremento no teor de óleo essencial em menta (Mentha arvensis) (BONATO et al, 2009), acréscimo na massa fresca de brócolis (PULIDO et al, 2017) (v v -1 ). Para a aplicação nas plantas, o Phosphorus foi diluído em água destilada na proporção de 0,5 mL L -1 .…”
Section: Introductionunclassified
“…not exclusive to these systems (Brasil, 2014). Pulido et al (2017) demonstrated an increase in broccoli (Brassica oleraceae L. var. itálica) biomass through the use of Sulfur 6CH, Silicia terra 6CH, Carbo vegetalis 30CH and Sulfur 30CH.…”
Section: Introductionmentioning
confidence: 99%